Indoor Environmental Quality - Godish, Thad (CRC Press, 2009)
When we think of indoor pollution, we usually think of conditions originating from faulty ventilation systems, second hand smoke, and other air borne pollutants. Taking an in-depth, hard science look at the problems of indoor environmental pollution, Indoor Air and Environment Quality covers all the major indoor contaminants - inorganic, organic, and biological.